Outcomes of transoral robotic surgery: a preliminary clinical experience - Hurtuk, Agnes (Otolaryngol Head Neck Surg, 2011)
OBJECTIVE: To report long-term, health-related quality of life (HRQOL) outcomes in patients treated with transoral robotic surgery (TORS). STUDY DESIGN: Prospective clinical study on functional and HRQOL outcomes in TORS. SETTING: University tertiary care facility. SUBJECTS: Patients who underwent TORS at The Ohio State University Medical Center. METHODS: All patients undergoing TORS were asked to complete the Head and Neck Cancer Inventory before treatment, and at 3 weeks, 3, 6, and 12 months postoperatively. Demographic, intraoperative, clinicopathological, and follow-up functional data were collected for each patient. RESULTS: Sixty four patients who underwent TORS were enrolled with a median age of 56.8years. A total of 113 TORS procedures were performed. Mean follow up time was 16.3 ± 7.49 months (range 6 to 33). Majority of TORS were performed for squamous cell carcinoma (88%). No patients experienced immediate postoperative complications, with all of the patients tolerating an oral diet without any airway compromise on the day of surgery. There was a decrease from baseline in the speech, eating, aesthetic, social, and overall QOL domains immediately after treatment. At the one year follow up, the HRQOL scores in the aesthetic, social, and overall QOL domains were near baseline. Patients with malignant lesions had significantly lower postoperative HRQOL scores in the speech, eating, social, and overall QOL domains (p<.05). Forty nine patients (77%) underwent adjuvant radiation therapy (RT), and 61% had chemoradiation (CRT) therapy. Patients who underwent adjuvant XRT or CRT had lower postoperative scores in the eating, social and overall QOL domains, compared to those who did not (p<.05). CONCLUSION: TORS is a safe procedure with good functional and HRQOL outcomes. Patients who undergo TORS for malignancies and receive adjuvant therapy tend to have lower HRQOL outcomes. TORS is a promising future alternative surgical treatment for laryngopharyngeal tumors.